Utilising artificial intelligence for teaching English pronunciation in Filipino students’ classes - Akromu Wajihan Qori; Rita Inderawati (Universitas Sriwijaya, 2025)
Proper pronunciation skills in English are essential for fluent communication and academic and professional success. However, Filipino students often face challenges in mastering pronunciation due to the differences in phonetic systems between English and their native language. On the other hand, the development of artificial intelligence (AI) has brought innovations in language learning, especially in pronunciation teaching. This study aims to explore the effectiveness of AI-based tools in improving Filipino students' English pronunciation. Then, identify the challenges and opportunities in applying AI to English pronunciation teaching. Then, understand the extent to which AI technology can support students' self-directed learning. This study employs a qualitative approach, utilising a case study method. Data were collected through semi-structured interviews using Zoom with six Filipino students. Then, the data were analysed through data condensation, data presentation, and conclusion drawing and verification. The results showed that AI is effective in improving Filipino students' English pronunciation by improving intonation, articulation, and confidence through direct feedback. However, challenges such as technological issues, unclear feedback, and a lack of cultural awareness in AI need to be addressed to better suit the language and cultural backgrounds of students. Although AI has great potential in language acquisition, technological limitations and cultural relevance can hinder its effectiveness, with careful data analysis ensuring the reliability of the findings as well as providing in-depth insights into students’ experiences in using AI. It can be concluded that AI has great potential in improving Filipino students’ English pronunciation learning.